Pengaruh Transformasi Digital dan New Media pada Perilaku Masyarakat di Ruang Digital - Putri Bilanova Nurya Mahesa; Irwansyah Irwansyah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The main problem in communication is the many changes in the form of communication media along with digital transformations in media communication. Changes in the community's approach in dealing with what media is used to convey messages. The purpose of this study is to explain how changes in communication media among the network community and affect people's lifestyles and needs in the use of various communication platforms in the digital world that affect daily, professional, educational and various other needs. This study uses a qualitative method with a literature review or desk review approach.